The University: a Reengage with its Fundamental Purpose - Ruth Alexandra Ramos Villacís; Mayra Alexandra López Villagrán; Danilo Fernando Vaca Pérez; Silvia Alexandra Laica Sailema (Medisur, 2023)
The university is the repository of universal culture and science. They have all taken on what we call scientific research. From the beginning, it obeys the vocation of thoroughly researching the matter of all sciences in order to impart the results of the investigation to its students. This article reflects on the development of the university and its relationship with scientific research. It is verified that the university is not due to a social purpose, but to the scientific advance that promotes progress and trains competent professionals, to cultivate and develop knowledge, and for this it is necessary to hire the best scientists. The research has to start from the need to recognize problems, and they have to be approached realistically, so that, if it is not possible to carry it out at first, the resources and capacities are generated to undertake a possibly very difficult task, necessary for society. All university establishments must be clear that knowledge is cumulative, that it cannot be researched without prior knowledge, that if something does not fit into what is known and requires the creation of new science or technology, this will necessarily have to be founded in what scientists know, so that scientific research will necessarily produce new knowledge that may or may not be predictable.